2020
DOI: 10.1007/s10103-020-03144-6
|View full text |Cite
|
Sign up to set email alerts
|

Stokes polarimetry-based second harmonic generation microscopy for collagen and skeletal muscle fiber characterization

Abstract: The complete polarization state of second harmonic (SH) light was measured and characterized by collagen type I and skeletal muscle fiber using a Stokes vector-based SHG microscope. The polarization states of the SH signal are analyzed in a pixel-by-pixel manner and displayed through two dimensional (2D) Stokes vector images. Various polarization parameters are reconstructed using Stokes values to quantify the polarization properties of SH light. Also, the measurements are extended for different input polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…R-ratio has been successfully used to differentiate normal and malignant tissues in lung, breast, thyroid, and pancreas 11 13 , 16 . The value of DCP is closely related to the R-ratio in non-scattering tissue and reflects the disorder and depolarization in the sample 28 , 29 . SHG-CD depends on the R-Ratio, out-of-plane fiber tilt angle and polarity, and the phase retardance between the achiral and chiral susceptibility components 10 , 24 , 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…R-ratio has been successfully used to differentiate normal and malignant tissues in lung, breast, thyroid, and pancreas 11 13 , 16 . The value of DCP is closely related to the R-ratio in non-scattering tissue and reflects the disorder and depolarization in the sample 28 , 29 . SHG-CD depends on the R-Ratio, out-of-plane fiber tilt angle and polarity, and the phase retardance between the achiral and chiral susceptibility components 10 , 24 , 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the developments using nonlinear light-matter interactions found an important perspective in structural molecular and biological imaging with the only drawback, in some cases, of requiring high illumination intensities [204]. Stokes polarimetry based on second harmonic generation provided new insights into collagen and skeletal muscle fibres [205] coupled with interesting solutions in terms of models and calibration procedures [206]. Moreover, approaches focused on optimizing imaging depth of scattering tissues [207] consolidated important label-free protocols towards the evaluation of bone-engineered materials [208].…”
Section: The Intelligent Microscope: An Examplementioning
confidence: 99%
“…Nataliia Pavlyukovich et al [9] demonstrated Stokes polarimetric imaging could be used for early detection of erythrocytes membrane disorders, which was meaningful for the diagnosis and treatment of most diseases of internal organs such as coronary artery disease and type 2 diabetes. Mazumder et al [10] used Stokes polarimetry to investigate the molecular structure of second harmonic generation active molecules such as collagen type I and myosin, which means Stokes polarimetry has great potential in the field of molecular structure in biomedicine. Besides, it is worth emphasizing that Stokes polarimetric imaging requires the circularly polarized light as the incident light, which is due to the circularly polarized light has strong polarization memory and is insensitive to the orientation of the sample with respect to the measurement system.…”
Section: Introductionmentioning
confidence: 99%